Citizens Without Robes: On the Deliberative Potential of Everyday Politics. Issue 2 (14th October 2020) - Chambers, Simone
This essay is a sympathetic critical comment on Cristina Lafont's recent book, Democracy without Shortcuts: A Participatory Conception of Deliberative Democracy . I focus primarily on the arguments in the final chapters of the book that introduce a deliberative democratic re-interpretation of judicial review. Lafont appeals to the evocative imagery of citizens in robes and suggests that contesting legislation at the level of the supreme court does not take questions out of the public sphere and into the legal domain but rather brings questions of right and constitutionality into the political domain. The institutional possibility for individual citizens to challenge any law and thus launch a broad public debate that demands justifications and reasons is the heart of Lafont's conception of participatory deliberative democracy. I find this a powerful and compelling defense and understanding of judicial review. I question, however, what appears to be a narrowing of deliberative democracy to constitutional contestation and so an abandonment of everyday politics where issues, debates, and controversies are not structured by the constraint of constitutional discourse. I argue that the focus on constitutional politics, made necessarily by her public reason requirement, narrows the range of her theory and appears to leave everyday politics outside the scope of deliberative democracy.